Marginal and Para-Marginal Technique in Late Germectomy of Lower Third Molars - Francesco Saverio Ludovichetti; Sergio Mazzoleni; Manuel Menin; Roberta Gaia Parcianello; Francielle Romanowski; Edoardo Stellini; Andrea Zuccon (MDPI AG, 2023)
Introduction: Third molar surgery can cause post-operative complications to the patient due to the presence of a wound from the incision. This study aimed to compare marginal flap with para-marginal flap on postoperative complications by the measurements on pre and post-surgical plaque index (PI), bleeding on probing (BoP), maximum opening of the mouth (MOM), pain perception (PP) and post-surgical tumefaction (PT). Methods: In this double-blind randomized clinical trial, 40 patients were recruited and randomly allocated in two groups. In Group 1, third molar extraction was carried out after a marginal flap design was performed, while in Group 2 a para-marginal flap was performed. Plaque index, bleeding on probing, maximum mouth opening, and distal probing were assessed right before and one week after surgery, while post-operative pain perception and post-operative swelling were accounted one week following surgery. Results: Statistically significant differences were reported between treatment groups, as the para-marginal flap led to better outcomes for all the measured indexes. Conclusions: The para-marginal flap design may decrease the occurrence of post-operative complications and discomforts after mandibular third molar surgery, compared to marginal flap design.